Utilización de raciones suplementarias a base de follaje de yuca (Manihot esculenta) en la alimentación de vacas lecheras en la Quinta Experimental Punzara de la UNL - Moncayo Peña, Ángel Richard (2017)
This research study was carried out in the Experimental Country-House “Punzara” of the National University of Loja, with the purpose of helping to improve levels of milk production in Holstein friesian cows, conserved under grazing conditions, through the use of supplementary rations developed based on cassava foliage. Four rations were evaluated with different levels of inclusion of cassava foliage, gotten the following treatments: T1: ration without cassava foliage (witness); T2: with 10%; T3: with 20% and T4: with 30% of cassava foliage in its structure. Four Holstein cows of different ages were used with an average weight of 490 kg and an average production of 7.5 l/d, distributed according to design of Latin square 4 x 4, with four treatments and four periods. The variables studied were: bromatological composition of experimental rations; consumption of food, milk production, milk quality, change in weight and profitability. The results show that the inclusion of different cassava foliage levels, improved protein content of experimental rations from 14.61 in the control group to 15.04% for T2; Likewise, it was showed a higher consumption of food in the treatment three and four (20-30% of cassava foliage) which generated an increase of the milk production of 2.9 l/cow/day treatment three; the weight of the individuals did not provide significant variations at the end of the experiment. Similarly, the organoleptic characteristics and quantification of protein in milk, were not changed. However, the fat content evidenced a progressive decrease as the percentage of cassava is increased in the ration, so the four treatment was the lowest in (30% FY). Finally, the profitability was acceptable in the rations with cassava foliage; so it is concluded that the use of supplementary rations based on cassava foliage, are a technically and economically viable alternative to improve the production of milk in the province of Loja.